The Effect of News Websites’ Design Quality on E- loyalty and Electronic Word of Mouth (e-wom) (Case Study: Allameh Tabatabaee University, Tehran) - Mohammad Reza Karimi Alavijeh; Sheida Ahmadi (Journal of Information Technology Management)
News websites’ design quality plays an important role in retention time and increasing visitors’ motivation in order to maintain loyalty and e-wom. Therefore, these websites are trying to achieve this competitive advantage through improving their websites’ design quality. The purpose of this research is to examine the effect of design quality of News websites on e-loyalty and e-wom. This article is applied in purpose, and is correlational descriptive-survey in terms of data collection. The population of the research includes the students of Allame Tabatabaee University who have at least once visited News websites. A sample of 374 students was selected using proportional stratified method and data was collected using a questionnaire. Finally, the hypotheses were tested using structural equation model (SEM) and SPSS, LISREL software. The results of the study indicate that websites’ design quality has a direct and significant effect on visitors’ pleasure and perceived quality of information and has indirect and significant effect on e-Satisfaction, e-trust, e-loyalty and e-wom.